Morphological Variations in the Accessions of Colocasia esculenta (L.) Schott. and Xanthosoma maffafa (L.) Schott. Exposed to Sodium Thiosulphate and Graphite Powder Treatments in Nigeria - Florence O. Ajah; Julian O. Osuji; Geoffrey O. Anoliefo (Archives of Current Research International, 2017)
Aim: To investigate the morphological variations in the accessions of Colocasia esculenta and Xanthosoma maffafa exposed to two oilfield chemicals. Study Design: The Randomized Complete Block Design was used for this study. Place and Duration of Study: The Ecological Research Centre of the University of Port Harcourt, Nigeria between April 2015 and June 2016. Materials and Methods: Graded quantities of 5, 10, 20 and 40 mg/kg of sodium thiosulphate and graphite powder were applied to each accession while the control experiment lacked the oil-field chemical additives. Results: Observations indicated that the differences in plant height, leaf area, girth and yield between treatments were not significant at 5%, but the differences in plant height, leaf area and yield between accessions were significantly different at P=.05. The differences in girth among accessions were however, not significant at P=.05. Accessions treated with graphite powder had higher values of mean height, leaf area and girth compared to accessions treated with sodium thiosulphate. Accessions treated with sodium thiosulphate had higher mean yield than those treated with graphite powder. Other morphological variations observed as a result of the chemical treatments included malformed leaves, different number of leaves per stand, stem colour difference and plant death. Conclusions: Cocoyam accessions have been established to be poor environmental bioindicator. Further studies were encouraged in order to obtain a clearer understanding of the potentials of the chemicals employed in the present study to cause other invisible genotoxic effects on the test plants.